Public Sector Property Asset Management - Ngwira, Malawi; Manase, David (Malden, MA : Wiley-Blackwell, 2016)
In many public sector organisations, there has been little or no adoption of a proactive asset management strategy. Where an extensive property portfolio exists, this can result in poor overall utilisation of the portfolio, exemplified by excessive vacant property or properties not being put to best use. In such situations there is a risk that the building stock deteriorates more rapidly than expected, leading to expensive maintenance and repair charges. Lack of a proactive asset management strategy will impact on the services delivered by such organisations. Public Sector Property Asset Management covers all aspects of asset management in the public sector, including the overall concept, the development of asset management strategies and the implementation of asset management practices. It evaluates asset management strategies, processes and practices to show how effective management of property assets support business activities or service delivery functions. The reader will understand the importance of improving decision-making through the recognition of all costs of owning and operating those assets throughout their lifecycle, leading to improved business process activities or service delivery functions which greatly assist in meeting the social and economic objectives of such organisations. Written for all practitioners currently involved in asset management, the book will also be useful in the university environment, to those teaching, researching or learning about asset management in the public sector.
6.4 Purpose and content of an AMP6.5 Content of an AMP; 6.6 Review of current property assets; 6.6 Chapter summary; References; Index; End User License Agreement.
Title from resource description page (Recorded Books, viewed May 02, 2016).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Business; Affaires; business (commercial function); BUSINESS & ECONOMICS -- Real Estate -- General; Business